2011
DOI: 10.1177/0093650210378518
|View full text |Cite
|
Sign up to set email alerts
|

From Podium to Living Room

Abstract: The primary goal of this study is to investigate whether and how elite debates stimulate citizens to take part in information seeking and conversation, two common forms of citizen communication that have been theorized as crucial to public deliberation and political engagement. Drawing on national survey data, this study finds that debate viewing was positively related to news consumption and political conversation. The data further suggest that part of these debate effects is mediated by either campaign inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Previous research on televised debates examined verbal and nonverbal communication modes separately, focusing on one or the other (Adam 2000;Benoit and Sheafer 2006;Cho and Choy 2011;Exline 1985;Fracchiolla 2011;Reinemann and Maurer 2005). However, this article suggests that examining verbal and nonverbal communication together is preferred, as it can provide new insights into the study of televised debates and offer a more satisfactory explanation for why contenders succeed or fail.…”
Section: Verbal=nonverbal Discrepancy and Nondiscrepancy In Politicalmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous research on televised debates examined verbal and nonverbal communication modes separately, focusing on one or the other (Adam 2000;Benoit and Sheafer 2006;Cho and Choy 2011;Exline 1985;Fracchiolla 2011;Reinemann and Maurer 2005). However, this article suggests that examining verbal and nonverbal communication together is preferred, as it can provide new insights into the study of televised debates and offer a more satisfactory explanation for why contenders succeed or fail.…”
Section: Verbal=nonverbal Discrepancy and Nondiscrepancy In Politicalmentioning
confidence: 97%
“…Even though this pattern of communication is nondiscrepant, it can be scathing and hurtful in how the message is conveyed. In this regard, it is worth recalling that although persuasion theories argue that negative information is more persuasive than positive information (Reinemann and Maurer 2005), recent studies of candidates in televised political debates suggested that a message that is too negative can arouse dislike and undermine the credibility of the candidate and his or her messages (Allen and Burrell 2002;Benoit and Sheafer 2006;Cho and Choy 2011). T. Grebelsky-Lichtman…”
Section: Verbal=nonverbal Discrepancy and Nondiscrepancy In Politicalmentioning
confidence: 99%
“…Previous research has empirically documented the mediating role of emotions in the effects of political information consumption. For example, Cho and Choy (2011) found negative emotions mediate the relationship between debate viewing and political conversations among partisans. The positive impact of pro-attitudinal news exposure on political participation is mediated by anger (Wojcieszak, Bimber, Feldman, & Stroud, 2016).…”
Section: Mediating Roles Of Anger and Fearmentioning
confidence: 99%
“…4 Numerous studies have shown that watching a debate fosters knowledge about the candidates and the issues and increases political interest and turnout (see, e.g. Benoit et al 2003;Cho and Choy 2011;Maier and Faas 2011). However, when candidates decide whether they want to participate in a debate, their primary goal is probably not to educate the electorate.…”
Section: Factors Influencing the Broadcasting Of A Televised Debatementioning
confidence: 99%